2016
DOI: 10.1002/adfm.201601732
|View full text |Cite
|
Sign up to set email alerts
|

Mo Doping Induced More Active Sites in Urchin‐Like W18O49 Nanostructure with Remarkably Enhanced Performance for Hydrogen Evolution Reaction

Abstract: Exploring highly efficient and inexpensive hydrogen evolution reaction (HER) electrocatalysts for various electrochemical energy conversion technologies is actively encouraged. Herein, a 3D urchin‐like Mo‐W18O49 nanostructure as an efficient HER catalyst is reported for the first time. The obtained Mo‐W18O49 catalyst exhibits excellent electrocatalytic activity toward HER with small onset potential and Tafel slope. The prepared Mo‐W18O49 electrode shows excellent durability after a long period. Density functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(110 citation statements)
references
References 53 publications
4
97
0
Order By: Relevance
“…In parallel, the peaks at 229.8, 231.5 and 233.0 eV are attributable to Mo 4+ , Mo 5+ and Mo 6+ , which are assignable to MoO 2 and MoO 3 . Three peaks can be seen in the O 1s XPS spectra (Figure c) for all the samples, which can be attributed to O−Mo (530.8 eV), oxygen vacancies (531.7 eV) and O−C (533.0 eV), respectively. The high‐resolution XPS spectrum of C 1s (Figure d) for all the samples can be regarded as C−Mo (284.3 eV), C−C/C=C (284.8 eV), C−P (285.1 eV) and C−O (286.3 eV), respectively.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…In parallel, the peaks at 229.8, 231.5 and 233.0 eV are attributable to Mo 4+ , Mo 5+ and Mo 6+ , which are assignable to MoO 2 and MoO 3 . Three peaks can be seen in the O 1s XPS spectra (Figure c) for all the samples, which can be attributed to O−Mo (530.8 eV), oxygen vacancies (531.7 eV) and O−C (533.0 eV), respectively. The high‐resolution XPS spectrum of C 1s (Figure d) for all the samples can be regarded as C−Mo (284.3 eV), C−C/C=C (284.8 eV), C−P (285.1 eV) and C−O (286.3 eV), respectively.…”
Section: Resultsmentioning
confidence: 86%
“…It is shown that the performance of W‐MoO 2 /MoC@PC ( η 20 =209 mV) is superior to that of Mo 2 C/C‐lamellas ( η 20 =220 mV), Mo x C‐G hybrids ( η 4 =475 mV), Mo 2− x Fe x C ( η 5 =240 mV), commercial Mo 2 C particles ( η 20 =225 mV), Mo 2 C nanoparticles supported on XC‐72R carbon black ( η 8 =200 mV), Mo 2 C nanowires ( η 20 =220 mV) and Mo 2 C nanosheets ( η 20 =260 mV) synthesized via pyrolysis of their MoO x /pphenylenediamine hybrid precursors, MoWON/NGR ( η 20 =270 mV) and so on. The performance of W‐MoO 2 /MoC@PC is inferior to that of Co 6 Mo 6 C‐G ( η 20 =183 mV), Mo‐W 18 O 49 ( η 20 =75 mV), MoO 2 @PC‐RGO ( η 20 =90 mV), NiMo‐NGTs ( η 20 =79 mV), and so on. The comparison reveals that W‐MoO 2 /MoC@PC exhibits comparable HER catalytic activity in comparison with most other Mo‐based nanostructures.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Considering this, defect‐rich W 18 O 49 , the only nonstoichiometric oxide composition of tungsten that can be isolated in a pure phase, might be an ideal candidate due to its intrinsically weak binding with hydrogen . In this case, however, the main challenges turn out to be: 1) maximizing the exposure of possible active sites (i.e., the W sites) and 2) the activation of N≡N to accelerate the sluggish NRR kinetics.…”
Section: Figurementioning
confidence: 99%